THE ROLE OF BRAND IMAGE IN MEDIATING THE EFFECT OF E-WOM ON REPURCHASE INTENTION AT THE FRONTIER HOUSE COFFEE SHOP - Ni Komang Intan Widiari; Ni Nyoman Kerti Yasa (Adisam Publisher, 2026)
The growing number of coffee shops in Denpasar, Bali has created intense market competition, pushing businesses to find effective ways to sustain consumer repurchase intention. In the digital age, E-WOM has emerged as a key factor shaping how consumers perceive brands and make purchasing decisions. This study aims to analyze the influence of E-WOM on repurchase intention and explore the mediating role of brand image at The Frontier House Coffee Shop, Denpasar. A quantitative method was adopted, with data collected through online questionnaires distributed to 120 respondents using purposive sampling. Data were then processed through path analysis, Sobel test, and VAF. Results show that E-WOM has a positive and significant effect on both repurchase intention and brand image, while brand image similarly contributes positively to repurchase intention. Mediation analysis further confirms that brand image acts as a partial mediator between E-WOM and repurchase intention. These findings suggest that favorable online reviews and active digital engagement can reinforce brand perception and motivate customers to return. Accordingly, coffee shop operators are encouraged to actively manage their digital reputation and consistently strengthen brand image as a long-term strategy for building customer loyalty and sustaining repurchase behavior.